(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review summarizes current knowledge on the pathophysiology, clinical features, diagnosis, and management of food allergies. IgE-mediated reactions to common allergens such as milk, eggs, peanuts, and shellfish can range from mild symptoms to anaphylaxis. Diagnosis involves patient history, IgE testing, and food challenges. Management includes allergen avoidance, emergency preparedness, and education. New therapies like oral and epicutaneous immunotherapy show promise. The review highlights evidence-based strategies and the need for further research to improve care and quality of life.